Neuroprotective potential of marine algal antioxidants - Nyiew, Ke-Ying *; Ngu, Ee Ling; Wong, Kah Hui; Goh, Bey Hing *; Yow, Yoon Yen * (Academic Press, 2023)
Marine algae have been traditionally consumed as part of the diets of Asian, African, and North American cultures. Nowadays, they are also utilized in food processing and cosmetics. Marine algae–derived bioactive compounds, many of which are antioxidants, are of great interest to researchers in the field of nutraceutical and pharmaceutical research. Various species of marine algae have exhibited neuroprotective and neuroregenerative properties. Thus there is a growing interest in the neuroprotective potential of marine algal antioxidants, such as phlorotannins, sulfated polysaccharides, and carotenoids. Marine algal antioxidants have been shown to attenuate the damaging effects of oxidative stress in both in vitro and in vivo studies. Although our knowledge of the neuroprotective activities of marine algal antioxidants is still limited, the potential of these compounds for use in treating neurodegenerative diseases and brain injuries is promising.